Flexibility as a binding requirement for sustainable planning and design of the social residential environment: The case of the city of Boussaâda - Hadji, Mouhamde; Dib, Belkacem (Journal of Architecture and environment of child, 2024)
The modern residential environment, especially directed to low-income groups, revealed a large gap between the design thought that created it and what its occupants aspire to, in addition to its lack of adaptability. Despite the negatives declared in the country of its adoption, it has been replicated within the Algerian housing policy. Its results did not differ from its predecessor, and their manifestations are evident in the random modifications that characterize the urban landscape. From this standpoint lies the importance of adopting design flexibility as a new concept to improve and upgrade the quality of the residential environment, which seeks to ensure its sustainability, which in turn aims to make optimal use of the latter within its life span. The research methodology relies primarily on the post-occupancy evaluation process in order to measure the degree of compatibility of the collective social residential environment - which lacks the concept of flexibility - with the requirements, perceptions and aspirations of its users. In other words, measuring the extent to which the absence of the concept of design flexibility at the level of this environment affects residential satisfaction, regarding Through an analysis of a residential sample in the city of Boussaâda, which consists of two social housing complexes (110 dwellings and 96 dwellings), then using the famous Chi-square statistical analysis for independence, we can extract the factors affecting residential satisfaction and compare them with those that Habraken adopted in the concept of design flexibility.